Dyskurs modernizacyjny a świat przeżywany młodych pracowników nauki. Analiza form i treści aktywności w dyskursie publicznym = Discourse of modernization and the world lived by young researchers. Analysis of the activity forms and content in public discourse - Messyasz, Karolina (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article is the analysis of public discourse concerning the reforms of science and higher education in Poland, the effects of which largely affect young researchers and determine their careers and future social status. The author treats these transformations as Habermas` "crisis" resulting from the dominance of technocratic consciousness. This situation generates both specific scenarios written by politicians/economists/experts/officials for young researchers, as well as certain adaptation strategies of the researchers themselves. The empirical part of the article is the analysis of the public discourse in "Gazeta Wyborcza" and "Tygodnik Powszechny" concerning the reforms of Polish science involving symbolic elites and young researchers.
Keywords: young researcher; discourse of modernization; public discourse; world lived; młody badacz; dyskurs modernizacji; dyskurs publiczny; świat przeżywany